Cybersecurity Risks in Vehicular Networks: Evaluating the CAN Bus 2.0 Through Real-World Testing - Vahala, Oskari (My University, 2025)
Modern passenger vehicles rely on internal communication networks such as Control Area Network (CAN), Local Interconnect Network (LIN) and wireless networks that support functions like smartphone integration and key fobs. Using these technologies makes the wiring harness of the car lighter, economical and easier to troubleshoot but it also introduces risks related to cybersecurity. This thesis evaluates the cybersecurity posture of the CAN bus through both literature review and real-world experimentation. The study examines the common vehicular communication protocols such as CAN and LIN from a cybersecurity perspective while introducing the common attack types such as injection, replay, DoS and Man-in-the-Middle attacks as well as associated countermeasures. The security of the CAN bus is tested using a Volvo V50 passenger car with a CAN USB interface to demonstrate attacks described in the theoretical part. Findings reveal that functions such as electric windows and the instrument cluster could be easily manipulated via the CAN bus. Additionally it was shown that CAN connected electric control modules could be selectively disabled (bus off) by injecting malformed frames to the CAN bus. CAN bus does have built-in error detection and correction functions but lacks the functionality to detect and prevent intentionally malicious actions. Literature review supports the fact that even more modern cars are vulnerable to the same attack types. Recommendations for enhancing the cybersecurity of the CAN bus such as using IDS/IPS, firewall, encryption and freshness check are described. Most of the security features could only be implemented during the design and the manufacturing process of the car.
Keywords: CAN, LIN, vehicular cybersecurity